Perlindungan Hukum terhadap Pemegang Desain Industri yang Sama dengan Merek yang Berbeda - Ni Komang Monica Dewi Maheswari; I Nyoman Putu Budiatha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2021)
Industrial design and brand that has been registered could not be replicated, copied, or rented out without the consent of the owner of the design and brand. The design industry and brand need to be protected in order to create the conditions of the business world that is safe and fair. Right to intellectual property has an important role in protecting the inventors thought that in order to avoid the behavior of a cheat. It is due to intellectual property rights is a right that was born from the thpught which are outlined in a wide variety of creation and provide benefits for its creator. The law provides protection to holders of rights in the form of prevention of the business of cheating that make, use, sell, and distribute goods produced without the permission of the owner right. If there are people and companies who cheated on industrial design it can be given administrative sanctions or criminal sanctions in prison.